Controversies of Diffusion Weighted Imaging in the Diagnosis of Brain Death. Issue 4 (12th June 2013) - Luchtmann, Michael; Bernarding, Johannes; Beuing, Oliver; Kohl, Jana; Bondar, Imre; Skalej, Martin; Firsching, Raimund
ABSTRACT Imaging techniques as confirmatory tests may add safety to the diagnosis of brain death, but are partly not accepted either because they are too invasive, such as conventional arterial angiography, or because there is still lack of evidence of its reliability, such as magnetic resonance angiography. In this study the reliability of diffusion weighted imaging for the diagnosis of brain death was evaluated according in terms of its sensitivity and specificity. The apparent diffusion coefficients (ADC) of 18 brain dead patients were registered from 14 distinct brain areas. The mean ADC values of the brain dead patients were compared with normal controls of physiological ADC values of unaffected brain tissue. Despite a highly significant decrease of the mean ADC value in 16 patients, two patients showed mean ADC values that were within normal physiological range. An explanation may be the pseudonormalization of ADC values seen in stroke patients that depends on the time of the onset of the brain damage. We conclude, diffusion‐weighted imaging may provide additional information on damage of the brain tissue but is not a practicable confirmatory test for the reliable diagnosis of brain death.